(untitled) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
Aluminum and copper industry is an industry that is engaged in the manufacture of aluminum, copper, and cables and other materials and other components as well. This study aims to determine the net profit margin or NPM, return on investment or ROI, Earning per Share or EPS, and Return On Equity or ROE in the 2017-2021 period in aluminum and copper producing companies listed on the BEI, in addition to analyzing the relationship or the effect of NPM, ROI, EPS, and ROE on the value of the stock price in the company listed on the Indonesia Stock Exchange or BEI. The research method used in this research is Structural Equation Modeling or SEM with AMOS application. The results of the study show that the value of the Outer Loading Original Sample from the NPM is 0.79, the ROE is 0.90 and the ROI is 0.87 and the EPS is 0.91. So from the conclusion, the higher the value, the more representative the influence on stock prices. Of the 4 financial ratios, it was found that the indicator that has an influence on the value of stock prices is Earning Per Share or EPS with a value of 0.91 and the results of the study show that the value of the performance of this financial ratio with a share price value of 45% and for the remaining 54% have an effect on other factors outside of financial performance.